The Effect Of Wegos Assisted By Tiktok With The Problem-Based Learning Model To Improve Students' Mathematical Problem-Solving Skills Statistics Material For Eighth Grade Junior High School - Indira Maisyrisa Widyaningrum; Gugun M Simatupang; Yelli Ramalisa; Novferma Novferma (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
The mathematical problem-solving ability of junior high school students is still low, requiring contextual and innovative learning methods. This study aims to improve the problem-solving skills of eighth-grade students at SMP Negeri 10 Kota Jambi in statistics through Problem Based Learning (PBL) supported by Wegos media and TikTok videos. A quantitative approach with a quasiexperimental Nonrandomized Control Group Pretest-Posttest Design was applied. The sample consisted of an experimental class using PBL with Wegos and TikTok and a control class using conventional methods. Data were obtained from pretests and posttests, analyzed using the Shapiro-Wilk test, Mann-Whitney test, and Effect Size. The results showed a significant difference, with the experimental class achieving moderate improvement and a large effect size. As a result, PBL supported by Wegos and TikTok is effective in improving students’ mathematical problemsolving skills.